Predictors of weight progression among HIV infected adults on anti-retroviral treatment in Mekelle hospital, Tigray, Ethiopia: A longitudinal study - Ataklti Kiflu Arefayne; Hagazi Gebre Meles; Goitom Halefom Senbete; Kibrom Birhane Gebrelibanos; Letemichael Mezgebo Gebrekorkos; Yohannes Kinfe Gebreyohannes (PLoS ONE, 2025)
Background Human immunodeficiency virus (HIV) remains a significant global public health issue, causing over 35 million deaths until 2017. In 2013, 24.7 million people in sub-Saharan Africa were living with HIV with 1.5 million new infections and 1.1 million deaths. Evidences on weight progression among HIV patients in low resource settings are limited. Additionally, many of the previously conducted studies were cross-sectional. Therefore, this study aimed to examine predictors of weight progression among adult HIV infected patients on ART from January 2017 to December 2019 in Mekelle hospital, Tigray, Ethiopia. Methods Retrospective longitudinal study was conducted from March 2, 2020 to March 14, 2020 at Mekelle General Hospital, Tigray, Ethiopia. A total of 97 individuals were followed every six months for two years. STATA version15 was used for data analysis. Linear mixed model was used to examine progression of weight after the baseline measurement. Regression coefficients of the final model and their 95% confidence intervals were used as measures of association with p-value below 0.05 indicating statistical significance. Results Baseline median age of participants was found to be 35 years (IQR = 27.5 to 40). At baseline, 39.18% were underweight, 53.61% normal and 7.22% overweight. About one-fifth (19.59%) of the study subjects were diagnosed with tuberculosis infection. Patients who had normal weight at baseline lost 1.89 kg (β = −1.89, 95% CI: −3.11, −0.66) at 6 months compared to underweight patients. Patients with CD4 level of >350 cells/µL at baseline lost 2.53 kg (β = −2.53, 95% CI: −4.43, −0.63) weight lower than patients with CD4 level of <=350 cells/µL, at 24 months. Conclusion and recommendation From this study, it can be concluded that weight of participants is influenced by measurement and individual level factors implying the need to address measurement and individual level factors when dealing with weight progression.